Heavy‐Metal‐Free Quantum Dot‐Based Flexible Electronics. (29th November 2021) - Zhao, Tianshuo; Basu, Amrita; Ramasamy, Karthik; Makarov, Nikolay S.; McDaniel, Hunter; Kagan, Cherie R.
Abstract: Applications of flexible electronics typically depend less on high computational power, instead exploiting the advantages of devices with a high degree of deformation that are lightweight, disposable or degradable, and low‐cost.